A Re-Analysis of Lachish V and IV: Implications for the Debate on High Chronology - Bányai, Michael (Antiguo Oriente, 2026)
This study offers a new stratigraphic interpretation of Lachish Levels V and IV, identifying Level V as the site’s first monumental phase, dating to Iron IIa Middle, in the first half of the tenth century BCE, in accordance with High Chronology. The resulting synthesis brings Lachish into alignment with the contemporary monumental traditions of Beer-Sheba V and Ashdod IX, suggesting Judahite control of the Shephelah considerably earlier than has generally been assumed. Incorporating the architectural and chronological data from Lachish into this wider framework necessitates a recalibration of Iron IIa stratigraphy across the southern Levant, placing the beginning of large-scale Judahite urban fortification securely in the first half of the tenth century BCE. A critical case-by-case discussion of Ussishkin’s built-up foundation theory is offered as an addendum to the paper.